Self-perception of the well-being of the family caregiver of the elderly and sociodemographic characteristics - Hermelinda Avila Alpirez (Cultura de los cuidados, 2013)
Introduction: Self-perception dimensional well-being is related to characteristics of caregivers. Objective: To establish association of self-perception in dimensions of well-being and characteristics of caregivers. Method: Descriptive, analytical and correlational study. Sample 300 caregivers. Matamoros Tamaulipas, México. Questionnaires: Sociodemographic data, Barthel Index and Quality Life: dimensions physical, psychological, social; and spiritual, this, with alpha of Cronbach 0.69. Test Chi-square and Pearson’s correlation coefficient. Results: Features most them women, aged 42, married, daughter, literate, work home, low education levels, without work or income limited. Self-perception with significance general well-being, literacy and kinship; physical dimensions, age and gender; psychological, schooling, social, and spiritual kinship literacy, employment status, occupation and marital status. Discussion: Characteristics harm to caregivers to adverse effects of care and determine greater perception of load that alters dimensional well-being.